Digestion rate in larval Strongylocentrotus purpuratus during laboratory experiments with low protease inhibitor treatments - Hildebrand, Jasper; Chang, William Weijen; Hu, Marian Y; Stumpp, Meike (In: Hildebrand, J et al. (2024): Protease characterization of larval Strongylocentrotus purpuratus collected from La Jolla, USA [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.966001, 2024)
Strongylocentrotus purpuratus (Stimpson 1857) originally collected in November 2020 from La Jolla, USA (Lat: 32.842674; Long: -117.257767) were held in flow-through tanks which were filled with water from Kiel Fjord adjusted to 31.5 psu at GEOMAR Helmholtz Centre for Ocean Research Kiel at 10 °C. For experimental characterization of protein digestion between January and June 2021 S. purpuratus larvae were generated by gently shaking adult males and females and held in climate chambers at 15°C and 31.5 psu in the Christian-Albrechts-Universität zu Kiel up to 14 days under different food conditions. Using RT-qPCR analysis, expression patterns of four protease genes including an enteropeptidase, aminopeptidase, carboxypeptidase and trypsin were analyzed against the housekeeping gene Elongation factor 1-alpha 1 (EF1a). Total protease activity of larval extracts were analyzed under different pHs, at different sampling points and with protease inhibitors including Soybean Trypsin Inhibitor and Aprotinin. Alterations of larval in vivo digestion rates were characterized under inhibitor influence. For both inhibitors the initial incubation before starting the reaction was 45 min. Data are supplement to: Hildebrand et al. (2023) Characterization of digestive proteases in the gut of a basal deuterostome accepted for publication in Journal of Experimental Biology.
Keywords: algae; culture experiment; energetics; Laboratory experiment; physiology; protein; sea urchin; Strongylocentrotus purpuratus